Increasing the effectiveness of Virtual Learning during COVID-19 - Mahdieh Motie; Reza Dehnavieh; Khalil Kalavani (Archives of Community Medicine and Public Health - Peertechz Publications, 2020)
In recent decades we have seen a huge growth in higher education around the world. But the prevalence of COVID-19 put many problems in the school and universities and put them in serious challenges in various aspects of management [1]. Now the different methods that improve the learning process, gained interest in the many universities [2].